A Review of Refractometric Sensors Based on Long Period Fibre Gratings - G. Rego (The Scientific World Journal)
In the last decade refractometric sensors have attracted an increasing interest by the scientific community due to their ability to perform ambient monitoring, to assess food quality and safety, and also to the fact that they enable the development of label free sensors in the biomedical area. These advances result, namely, from the use of long period fibre gratings in the turning points and/or with thin films in the transition region that allows resolutions of 10−6 to changes in the refractive index of the surrounding medium. Resolutions exceeding 10−8 can also be achieved when long period fibre gratings are combined with evanescent field based devices. This paper reviews the recent path towards the development of ultrahigh sensitive optical fibre refractometric sensors.